Treatment response in patients with moderate-to-severe psoriasis who had inadequate response to prior secukinumab - Tai-Siang Chiu; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2019)
Background/Objective: Secukinumab is an effective treatment for psoriasis, and it has been reported to be effective in patients who failed on multiple prior biologics. However, treatment failure of secukinumab is possible and the alternative management in these patients remains poorly studied. Methods: We reviewed the treatment efficacy of all patients with moderate-to-severe psoriasis who used secukinumab as monotherapy and did not reach Psoriasis Area Severity Index 75 (PASI 75) response at week 16 (primary failure) or later (secondary failure). The treatment response of these patients during subsequent treatments was recorded. Optimal PASI improvement between weeks 12 and 20 and at the end of observation period was recorded. Results: Traditional systemic treatment (n = 4), etanercept (n = 1), adalimumab (n = 6), secukinumab weekly reloading (n = 2), or ustekinumab (n = 4) was administered in 16 patients (one with both ustekinumab and adalimumab). Six patients reached PASI 75 at week 16, including three (50%) with adalimumab. PASI 75 response was maintained in four patients at the end of observation period. Two (50%) of them used adalimumab, one used methotrexate plus acitretin, and the other used secukinumab. Conclusion: Adalimumab demonstrates better response in patients with refractory psoriasis to secukinumab. Traditional systemic medication and re-loading of secukinumab can also provide some benefits.